P-292 Laboratory performance in PGT-SR cases in carriers of chromosomal rearrangements. (30th June 2022) - Douglas, K; Odia, R; Campbell-Forde, M; Cardenas, D; Seshadri, S.S; Serhal, P; Saab, W
Abstract: Study question: Could laboratory outcomes, such as fertilisation and blastocyst formation rates be altered based on which partner carries a chromosomal rearrangement in PGT-SR cases? Summary answer: Blastocyst formation is significantly reduced when both partners carry a mutation, compared to patients carrying paternally derived translocations What is known already: Some research suggests that the presence of paternal translocations may significantly increase miscarriage rates in patients who conceive naturally, versus patients who conceive after PGT-SR. Additionally, there may be a trend towards a shorter time to livebirth when considering PGT-SR patients, versus those who conceive by natural conception. This could aid treatment choices for patients in this cohort. Research has evaluated laboratory and clinical outcomes for PGT-M patients and found that this cohort of patients have slightly higher success rates, when compared to PGT-SR patients. The commonality of these studies being multicentre warrants further investigation from a single centre ART. Study design, size, duration: An observational single centre study performing retrospective analysis of data for patients having PGT-M or PGT-SR between 2015 and 2020. After exclusion criteria were considered, this study evaluated laboratory findings for 484 patients. This included PGT-SR patients affected by reciprocal and Robertsonian translocations as well as PGT-M patients, who were the control group. Patients with more complicated chromosomal rearrangements were excluded from analysis. Participants/materials, setting, methods: IDEAS ® (V6.0) software was used to capture all laboratory details relating to the patient cohort. This included number of cycles, number of oocytes collected, oocyte maturity, fertilisation rate and blastocyst formation rate. The official PGT-M or PGT-SR reports were consulted for information related to the embryos tested for each patient. Genetic testing was performed by Igenomix, CooperGenomics or Reprogenetics. All variables were evaluated using Chi-Square to establish whether there were any statistically significant differences noted. Main results and the role of chance: A total of 5, 149 oocytes were inseminated and 3, 825 embryos were created from the 484 cycles included in this analysis. There were no significant differences in fertilisation rates for maternal or paternal mutations by direct comparison (p > 0.05). Of these, 2, 354 embryos formed blastocysts suitable for PGT-M or PGT-SR. Blastocyst formation rates were marginally statistically lower when both partners carried a mutation when compared to maternal or paternal translocations or exclusively paternal translocations, respectively (p = 0.047; p = 0.033). We observed a slight trend towards decreased fertilisation and blastocyst formation rates when maternal and paternal mutations were present, but this was not statistically significant. Limitations, reasons for caution: This study was limited by modest sample size; further research would include a larger cohort of patients. This study evaluated laboratory outcomes, but future research could assess clinical outcomes to establish any impact of the origin of chromosomal rearrangement on implantation, pregnancy, and live birth rates. Wider implications of the findings: This study suggests reduced blastocyst formation rates when both partners carry a mutation; this information may be used to counsel patients. It may impact the treatment options and number of embryo batching cycles prior to blastocyst culture for PGT. This could help to improve and better inform the patient experience. Trial registration number: IRB-001C02-01-22